Pharmacokinetics and bioequivalence study of two mosapride citrate formulations after single-dose administration in healthy Chinese male volunteers - Huang, Jun; Tian, Yuan; Zhang, Zun-Jian; Li, Jinheng; Cao, Xiaomei (Arzneimittelforschung, 2011)
The pharmacokinetics and relative bio-availability/bioequivalence of two formulations of mosapride citrate (CAS 112885-42-4) were assessed in this study. The study was conducted in 20 healthy Chinese male volunteers according to an open, randomized, single-blind, 2-way crossover study design with a wash-out phase of 7 days. Blood samples for pharmacokinetic profiling were taken up to 12 h post-dose, and mosapride citrate plasma concentrations were determined by a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. Based on the plasma concentration-time data of each individual during two periods, pharmacokinetic parameters, Cmax, AUC0−t, AUC0−∞ and t1/2, were calculated by applying non-compartmental analysis. Pharmacokinetic data for test and reference formulations were analyzed statistically to test for bioequivalence of the two formulations.After oral administration, the values of Cmax, Tmax, t1/2, AUC0−t AUC0−∞ for test and reference formulations were 68.48 ± 22.95 and 70.69 ± 23.78 ng/mL, 0.46 ± 0.20 and 0.49 ± 0.21 h, 2.30 ± 0.30 and 2.24 ± 0.28 h, 161.17 ± 52.75 and 171.37 ± 59.02 ng · h/mL, 165.76 ± 54.34 and 175.77 ± 60.54 ng · h/mL, respectively. Both primary target parameters, AUC0−∞ and AUC0−t, were tested parametrically by analysis of variance (ANOVA). Relative bioavailabilities were 95.3 ± 11.3% for AUC0−∞ and 95.2 ± 11.3% for AUC0−t. Bioequivalence between test and reference formulations was demonstrated for both parameters, AUC0−∞ and AUC0−t. The 90% confidence intervals of the T/R-ratios of logarithmically transformed data were in the generally accepted range of 80–125%. That means that the test formulation is bioequivalent to the reference formulation of mosapride citrate.
Keywords: Bioequivalence; CAS 112885-42-4; Gastroprokinetic agent; Mosapride citrate; Pharmacokinetics